2020
DOI: 10.1080/23311908.2020.1714833
|View full text |Cite
|
Sign up to set email alerts
|

Collective harmony as a moderator of the association between other-referent upward counterfactual thinking and depression

Abstract: The current study aimed to investigate a recently observed significant positive relationship between other-referent upward counterfactual thinking and depressive symptoms in a Filipino sample by exploring whether collectivist harmony may determine when other-referent upward counterfactual thinking confers risk for depression. An online survey was completed by 598 university-educated residents of the Philippines (M age = 29.74, SD = 10.27; Range = 18 to 71). As hypothesised, both other-referent upward counterfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 102 publications
1
5
0
Order By: Relevance
“…Findings further gave light to the Filipinos’ need for social connection and support in coping for their loss. The reports of participants’ desire for the company of their family and friends as they go through bereavement is consistent with the findings of Broomhall and Phillips (2020) discussing on how Filipinos are associated with having a collectivist culture since it is a common practice for them to seek yet obtain social support from other people. The statements above have shown how the friends and families of the participants showed empathy and connection with them, and how it helped with their bereavement.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Findings further gave light to the Filipinos’ need for social connection and support in coping for their loss. The reports of participants’ desire for the company of their family and friends as they go through bereavement is consistent with the findings of Broomhall and Phillips (2020) discussing on how Filipinos are associated with having a collectivist culture since it is a common practice for them to seek yet obtain social support from other people. The statements above have shown how the friends and families of the participants showed empathy and connection with them, and how it helped with their bereavement.…”
Section: Discussionsupporting
confidence: 83%
“…Being that the Philippines is associated with having a collectivist culture, it is a common practice for Filipinos people to seek and obtain social support from other people ( Broomhall & Phillips, 2020 ). This culture offers an insight to the deep sentimentality invested by Filipinos towards their deceased loved ones when they mourn - hinting the importance of social congregations and interactions in wakes and burials as being part of the process of Filipino mourning.…”
Section: Introductionmentioning
confidence: 99%
“…Other researchers have found that a collectivist orientation is linked to depression (Broomhall & Phillips, 2020;Knyazev, Kuznetsova, Savostyanov, & Dorosheva, 2017;Yang, 2016).…”
Section: Depression Mus Andmentioning
confidence: 93%
“…We computed an average score using the 3-item scores, and higher scores indicate higher levels of counterfactual thinking. 41 …”
Section: Methodsmentioning
confidence: 99%